A STUDY ON INVESTMENT PORTFOLIOS’ MIX OF ASSETS OF THE LIC OF INDIA - B. SHABEENA , DR. N. GUNASEGARI (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
In this research paper, an attempt has been made to analyze the portfolios’ mix of assets of the LIC of India after the liberalization of the Indian insurance industry. The time of the study has been taken from 2020 to 2024. To evaluate the data, time series analysis, common-size analysis, and percentage are used. Portfolio analysis considers the determination of future risk and return in holding various blends of individual securities. An integral part of any decision-making process should be the evaluation of the decision. So the selection of a portfolio of securities is important for the Life Insurance Corporation of India in the present scenario.